Síntese, caracterização e estudos biológicos envolvendo complexos de cobre(II) contendo hidrazidas e ligantes N,N-doadores - Paixão, Drielly Aparecida (2017)
This work describes the synthesis of twenty novel ternary copper(II) complexes with hydrazides (4-fluorophenoxyacetic acid hydrazide (4-FH), 4-nitrobenzoic hydrazide (4-NH), benzhydrazide (BH), 2-chlorobenzhydrazide (2-CH), 4-chlorobenzhydrazide (4CH), 2-methoxybenzhydrazide (2-MH) or 4-methoxybenzhydrazide (4-MH)) and N,Ndonor ligands (1,10-phenanthroline (phen), 2,2-bipyridine (bipy) or 4-4′-dimethoxy-2-2′bipyridine (dmb)). These complexes were characterized by elemental analysis (CHN), conductivity measurements, FT-IR, UV-Vis and high-resolution electrospray ionization mass spectrometry (HRESIMS). The structures of two coordination compounds were elucidated by single crystal X-ray analysis. In all the complexes, the copper is bound in a bidentate manner to hydrazide via the terminal nitrogen and the carbonyl oxygen, and to heterocyclic bases via their two nitrogen atoms. The labilization of the axial ligands in solution (perchlorate anions) result in the generation of compounds of type [Cu(N–O)(N– N)]2+. Regarding the clinical utility of these complexes, the cytotoxic activity of compounds was investigated in three tumor cell lines (K562, MDA-MB-231 and MCF7). Concerning K562 cell line, the complexes with 1,10-phenanthroline exhibit high cytotoxic activity and are more active than carboplatin, free ligands and [Cu(phen)2]2+. Considering the cytotoxicity results, further investigations for the compounds Cu(4FH)(phen)(ClO4)2 and Cu(4-NH)(phen)(ClO4)2∙H2O were performed. Flow cytometric analysis revealed that these complexes induce apoptotic cell death in MDA-MB-231 cell line and bind to DNA with K values of 4.38 × 104 and 2.62 × 104, respectively. Thereafter, thirteen copper complexes were evaluated for their trypanocidal and cytotoxic activities. Several complexes were more active than free ligands and benznidazole, a drug used in the treatment of Chagas disease. The selectivity index calculated for two copper complexes was higher than recommended for subsequent tests. These findings are very important and make these compounds candidates for preclinical studies in vitro and in vivo.